Facebook and its uses and gratifications: a study of Palestinian students at a Public University in Malaysia - Alakklouk, Bader; Mokhtar, Aida (Faculty of Communication and Media Studies (FCMS), Universiti Teknologi MARA, 2017)
This study explores the uses and gratifications theory on the use of Facebook among Palestinian students at a public university in Malaysia. The theory posits that individuals actively choose media channels or media content to satisfy their needs. In-depth interviews were conducted among 12 heavy users of facebook. These participants comprise Palestinian students of a public university in Malaysia. As it is, Facebook is a convenient platform to express ideas and opinions on the Palestine crisis making it popular amongst Palestinian users particularly with the Palestine-Israel conflict that is taking place now in the West Bank, Gaza Strip and Jerusalem. The findings of the study identify the needs gratified by Facebook: connecting, source of news and information, freedom of expression, entertainment and academic purposes. The reasons why Facebook gratifies the public university’s Palestinian students’ needs is because Facebook is perceived as a convenient platform, is a famous social networking site (SNS), provides entertainment and allows the freedom of expression. The participants pointed out three improvements that are required from Facebook: improving the privacy of users, cutting advertisements and allowing more freedom of expression.